The development of interrogative forms and functions in early childhood Cantonese. Issue 2 (April 2013) - Li, Hui; Tse, Shek Kam; Sin Wong, Jessie Ming; Mei Wong, Eileen Chin; Leung, Shing On
This study investigated question acquisition in Cantonese-speaking young children with a focus on the development of interrogative forms and functions. Data from a child Cantonese corpus (492 children aged 36, 48 and 60 months) were analysed. The main results were that: (1) all the interrogative forms and functions were produced by the three age groups and no age difference was found; (2) significant gender differences in favour of females were found; and (3) a significant form-function preference was obtained, with wh- and multiple questions being primarily used to seek information, and yes/no and rising tone/echo questions being largely used to request action.